Association of the PaO2/RDW ratio with 7-day mortality and risk of early invasive mechanical ventilation in ICU patients with delirium associated with ARDS: A retrospective cohort study from the MIMIC-IV database - Jiao Xu; Jun Jin; Shan Zou; Si-Hao Zheng; Qing-Shan Zhou; Jiang-Tao Deng (PLoS ONE, 2025)
Background Delirium is a common complication in patients with acute respiratory distress syndrome (ARDS) and is associated with poor clinical outcomes. However, studies investigating the associations between easily accessible biomarkers and early mortality or the risk of early invasive mechanical ventilation in this population remain poorly defined. This study aimed to investigate the association between the ratio of arterial partial pressure of oxygen to red cell distribution width (PaO2/RDW) and short-term outcomes in ICU patients with delirium associated with ARDS. Methods Data were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV, version 3.1), a large, publicly available critical care database that contains de-identified health records of patients admitted to Beth Israel Deaconess Medical Center. Adult ARDS patients with at least one positive Confusion Assessment Method for the ICU (CAM-ICU) evaluation were included. The primary outcome was all-cause mortality within seven days after delirium onset, and the secondary outcome was the initiation of invasive mechanical ventilation after ICU admission. Cox proportional hazards and cause-specific Cox regression models were applied to evaluate the associations between the PaO2/RDW ratio and clinical outcomes. Restricted cubic spline (RCS) modeling was used to explore potential nonlinear relationships, and subgroup analyses were performed to assess consistency across clinical strata. Results A total of 4,116 patients with ARDS were initially identified, and 1,665 patients with delirium were ultimately included in the final analysis. Compared with the highest PaO2/RDW tertile, patients in the lowest tertile had significantly higher risks of 7-day (adjusted HR = 2.12, 95% CI 1.46–3.09, P < 0.001) and 30-day mortality (adjusted HR = 1.72, 95% CI 1.33–2.22, P < 0.001). The lowest tertile was also associated with an increased risk of invasive mechanical ventilation (adjusted HR = 2.68, 95% CI 1.16–6.22, P = 0.021). Restricted cubic spline analysis revealed a U-shaped association between the PaO2/RDW ratio and 7-day mortality, with the lowest estimated hazard at approximately 6.7. Subgroup analyses showed consistent associations across age, sex, and comorbidity strata without significant interactions (P for interaction > 0.05). Conclusions The PaO2/RDW ratio was independently associated with 7-day mortality after delirium onset and with the early risk of invasive mechanical ventilation among ICU patients with delirium associated with ARDS. As an easily obtainable composite index, the PaO2/RDW ratio may serve as a convenient and informative biomarker for early risk assessment and clinical decision-making in critical care settings.